Terapi Massage Effleurage Pada Ny. G Terhadap Sensasi Proteksi Kaki Pasien Dengan Diabetes Melitus Di Desa Tambang Wilayah Kerja UPT Puskesmas Tambang - Fitri Zhella Destiana; Nila Kusumawati; Ridha Hidayat (Excellent Health Journal, 2025)
Diabetes Mellitus (DM) is a chronic disease caused by the body's inability to absorb carbohydrates, fats and proteins, resulting in high blood sugar levels (hyperglycemia). DM is one of the top 10 causes of death worldwide in 2022. One of the complications of DM is damage to the nervous system (neuropathy). Various actions are taken to prevent and control the occurrence of diabetic neuropathy. The non-pharmacological therapy given is massage to increase the sensation of protection in the feet. The massage therapy that can be applied is the effleurage massage technique, which aims to relax muscles and to improve blood circulation, reduce pain, reduce swelling and so on. This study aims to conduct an effleurage massage therapy intervention to increase the sensation of foot protection in DM patients. This study was conducted on September 6-8, 2024. This study conducted a 10g monofilament test to examine the sensation of foot protection. On the first day, the sensation of foot protection with a score of 5, after doing effleurage massage therapy for 3 days the score increased to 7. This shows that effleurage massage therapy has an effect on increasing the sensation of foot protection in DM patients. It is expected that the family can work together with the client to help the client to do effleurage massage therapy independently.